Dental Vacations: Healthcare and Holidays in India - Jain, Chirag; Shah, Rohit; Mitra, Dipika; Talati, Meenakshi; Vijaykar, Harshad; Dharne, Surbhi (International Journal For Research In Health Sciences And Nursing, 2018)
In-vogue 21st century, the popular term globalization has definitely conjured a plethora of development, the economic surge, integrated corporate dental offices, and contemporary approaches to health-seeking behaviour. Transnational medical travel has gained attention recently as a strategy for patients to procure cost-effective care of superior quality relative to that provided within their home countries. Dental tourism, a subset of medical tourism, involves individuals seeking dental care outside their local healthcare systems, coupled with a vacation. India has become a popular destination for foreign patients in recent times, particularly in dental care. India’s accessibility and availability of quality assured and cost-effective dental treatment, amalgamated with its myriad hues of culture and heritage has exponentially assisted the bloom of India in dental tourism. Humongous costs, lack of health insurance and dental benefits are key factors pushing low-income westerners to obtain cross-country dental care. Dental Tourism companies and corporate dental chains are advertising “all inclusive” travel packages that include dental procedures, hotel room reservations, side trips to tourist attractions, and airline tickets to attract international clients. With current governmental activities in full throttle, the tide of dental tourism promises to boost the economy of India manifold. The future is not near. It’s here!